Dietary acid load, IGF-1 single nucleotide polymorphism and bone resorption among postmenopausal Chinese women - Lim, Sook Yee; Mohd Shariff, Zalilah; Chin, Yit Siew; Vasudevan, Ramachandran; Chan, Yoke Mun (MDPI, 2018)
The interaction of dietary and genetic factors may affect the development of bone deterioration. This study investigated whether the effects of dietary acid load (DAL) on bone loss in postmenopausal Chinese women were moderated by the insulin-like growth factor-1 (IGF-1) single nucleotide polymorphism, a known gene that plays a role in the regulation of bone formation and bone remodeling. A total of 217 healthy participants were recruited from the National Council of Senior Citizens Organizations Malaysia. Serum collagen type 1 cross-linked C-telopeptide was used as a surrogate bone marker to assess bone resorption and Agena® MassARRAY genotyping analysis was used to identify the signaling of IGF-1 rs35767. The dietary acid load was measured by potential renal acid load score while physical activity was ascertained using the Global Physical Activity Questionnaire. Hierarchical regression was applied to test the main and interaction effects of DAL and IGF-1 genotypes in bone resorption. The result supported the diet-dependent acid-base balance theory that higher DAL was positively associated with bone resorption (β = 0.152, p = 0.031, F(6,207) = 2.11, sig-F = 0.036, R2 = 0.079). However, the results indicated that there was no significant correlation between IGF-1 and bone resorption, or any significant interaction between DAL and IGF-1. In conclusion, there was no moderating effect of IGF-1 on the relationship between DAL and bone resorption.